Are our COVID-19 response and recovery efforts in sync with the principles of disaster risk reduction?. - Lunga, W; Tirivanhu, P; Sobane, K; Musarurwa, C (HSRC Press, 2022)
Even before the emergence of COVID-19, the World Economic Forum's Global Risk Report highlighted complex, interconnected risks to humanity. How would countries mitigate the additional effect of a pandemic? HSRC researchers examined the effectiveness of South Africa's disaster risk reduction actions.